2001
DOI: 10.1191/096032701718890586
|View full text |Cite
|
Sign up to set email alerts
|

Human biokinetics of injected bismuth-207

Abstract: A healthy male volunteer received an intravenous injection of 207Bi as citrate. Levels of the tracer in blood and in excretion samples, and its retention and distribution within the body, were investigated by appropriate radioactivity measurements. Levels in blood fell very rapidly, with only 1% of the injection remaining at 7 h and only ca. 0.1% at 18 days. There was rapid initial excretion, with 55% lost during the first 47 h, principally in urine; however, longer-term losses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Estimated kidney doses of 9 to 13 Gy to the renal cortex from 225 Ac and its a-particle-emitting daughters, including 213 Bi, resulted in tubular epithelial necrosis and marked regeneration. Accumulation of 213 Bi or 212 Bi in the kidneys was consistent with biodistribution studies of nonchelated or free radiobismuth (28).…”
Section: Discussionsupporting
confidence: 74%
“…Estimated kidney doses of 9 to 13 Gy to the renal cortex from 225 Ac and its a-particle-emitting daughters, including 213 Bi, resulted in tubular epithelial necrosis and marked regeneration. Accumulation of 213 Bi or 212 Bi in the kidneys was consistent with biodistribution studies of nonchelated or free radiobismuth (28).…”
Section: Discussionsupporting
confidence: 74%
“…Renal uptake of 213 Bi has been shown in previous studies (Newton et al 2001). As free 213 Bi is constantly being generated by the decay of 225 Ac, it is anticipated to have an apparent effective half-life equivalent to that of 225 Ac.…”
Section: Discussionsupporting
confidence: 68%
“…They reported that a fraction of the inhaled environmental radon is not breathed out but passes from the lungs into the bloodstream and is taken up and retained by a number of tissues and organs. Taking into account that Newton et al (2001) found that 75% of the injected bismuth in the form salt in an adult man was retained in his body 6 h post administration, and that the physical half life of 214 Bi is two orders of magnitude lower than that of the 222 Rn, the observed changes in 214 Bi activity in the human body in the present study can be explained as follows. In another individual, they reported that the 214 Bi activity in his body was reduced by a factor of two within about 70 or 100 min after a 1-hlong exposure to radon-laden atmospheres and that the rate of decrease was dependent on the type of atmosphere (unfiltered and filtered air, respectively).…”
Section: Measurements Under Various Ventilation Conditionsmentioning
confidence: 61%